Implementation of a structured PL/I subset compiler - Goldberg, Colin Barry (Department of Computer Science, 2016)
The thesis describes the design and implementation of a PL/I subset compiler which produces a hypothetical stack code as output. The compiler was based on a Pascal compiler developed by N. Wirth and U. Amman of Eidgenössische Technische Hochschule, Zurich, and was itself written in the Pascal language. PL/I programs using the compiler can now be compiled and executed (interpretively) on the UNIVAC 1106 computer at U.C.T. The compiler was designed mainly as a teaching system. Its lesson is that structured programming is a powerful technique which facilitated its design and implementation.